(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Aim- The present research was conducted to study the prevalence of dry eye disease (DED) in adolescents due to long screen time doing a cross sectional study.Methods-A cross-sectional study was conducted in 140 patients in 10 to 19 years of age. DED was diagnosed using a structured questionnaire. To determine the impact of independent variables such as age, gender, refractive error, ocular allergy, meibomian gland disease on the probability of DED, a logistic regression model was developed. Statistical analysis was performed using SPSS version 24.Result- The mean age of study patients was 14.90±3.22 years. The prevalence of dry eye was calculated to be 34.28 (48140). Females showed higher preponderance to dry eye than males. Prevalence of dry eye increased as the age increased, from 33 in 10-14 years to 67 in 15-19 years. Presence of refractive error (p=0.002) and meibomian gland dysfunction (P=0.001) was found to be statistically significant.Conclusion- We estimated that 34.28 patients were diagnosed DED, prevalence is higher in females and increased with age. Fourty percent of the total subjects were found to have MGD.